Reuse of spent resin for aqueous nitrate removal through bio-regeneration. (1st July 2019) - Ye, Ting; Wang, Ke; Shuang, Chendong; Zhang, Guang; Li, Aimin
Abstract: Some commercial products of anion exchange resins have been used in removing aqueous nitrate, but their application has been limited by the spent resins and the brine-waste. In this work, the regeneration of nitrate-laden resin using denitrifying bacteria was investigated for the reuse of the spent resin without brine-waste discharge. The results indicate that the bio-regeneration contains two mainly processes of chemical regeneration (ion exchange) and bio-degradation (denitrification), in which the denitrification related to the inoculum amount was the limiting factor of bio-regeneration. The bio-regeneration time was reduced to about 4.0 h with increasing inoculum amount to 2.2 g VSS/L. It also reduced from more than 50.0 h–4.0 h with the decreasing resin amount from 5.0 g to 0.2 g in the saturation of 35.5 mg/g, and reduced from 12.0 h to 3.0 h with the resin saturation from 27.4 mg/g to 2.70 mg/g in the resin amount of 0.2 g under the inoculum amount of 2.8 g VSS/L. The comparation of bio-degradation rate between data with different resin amount and data with different resin saturation suggested that the spent resin with a high degree of saturation is favorable to bio-regeneration. The bio-regenerated resin can be reused with 11.6% of capacity loss in the initial 5 cycles and gradually reach a stable reusability. This decrease was attributed to the adsorption of protein-like substances onto resin rather than biomass attachment onto resin. This study proposes the reuse of spent resin by bio-regeneration in a reuse mode for the aqueous nitrate removal, with at least 87.5% reduction on the production of waste water from bio-regeneration process. Graphical abstract: Image 1 Highlights: The resin was completely bio-regenerated in ∼4 h with the inoculum of 2.2 g VSS/L. The bio-regeneration system reused for bio-regeneration at least 8 times. Bio-regeneration was limited by denitrification rather than ion exchange process. The resin with a high degree of saturation is favorable to bio-regeneration. Capacity loss was caused by fouling of protein-like substances rather than biomass.